2021
DOI: 10.1021/acsami.0c17867
|View full text |Cite
|
Sign up to set email alerts
|

Food and Beverage Ingredients Induce the Formation of Silver Nanoparticles in Products Stored within Nanotechnology-Enabled Packaging

Abstract: Nanotechnology-based packaging may improve food quality and safety, but packages manufactured with polymer nanocomposites (PNCs) could be a source of human dietary exposure to engineered nanomaterials (ENMs). Previous studies showed that PNCs release ENMs to foods predominantly in a dissolved state, but most of this work used food simulants like dilute acetic acid and water, leaving questions about how substances in real foods may influence exposure. Here, we demonstrate that food and beverage ingredients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 65 publications
(135 reference statements)
1
12
0
Order By: Relevance
“…Hydrophobic AgNPs capable of being incorporated within LPDE were synthesized in water and phase transferred to chloroform using our published method. 17 Dispersion of these AgNPs into LDPE was accomplished using a DSM Xplore 15 mL micro-compounder. Full details on these procedures are included in the ESI † section.…”
Section: Synthesis Of Agnps and Manufacture Of Agnp/ldpe Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrophobic AgNPs capable of being incorporated within LPDE were synthesized in water and phase transferred to chloroform using our published method. 17 Dispersion of these AgNPs into LDPE was accomplished using a DSM Xplore 15 mL micro-compounder. Full details on these procedures are included in the ESI † section.…”
Section: Synthesis Of Agnps and Manufacture Of Agnp/ldpe Filmsmentioning
confidence: 99%
“…On the other hand, we recently demonstrated that certain reducing ingredients commonly found in foods and beverages (e.g., monosaccharide sugars), or ingredients that can hydrolyze into reducing substances during storage (starches or complex sugars), are capable of converting ionic Ag migrated from packaging back into particulate Ag with various sizes and morphologies. 17 Because ionic and particulate Ag may exhibit different biological effects after oral exposure, 18 these prior findings suggest that the way in which food and beverage ingredients influence the fate of nanoparticulate food packaging additives should be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Although the detected amount was rather low (<10 ng/dm 2 this finding raised concerns associated with the potential intake of this nanomaterial by the consumer. In another study, Yang and coworkers reported that some Ag + ions were found to release from an AgNP/low‐density polyethylene sachet used to store food and beverage (Yang et al., 2021). More worryingly, the Ag + ions further converted to AgNPs upon reacting with the reducing ingredients (such as sugars) in food and beverage.…”
Section: Figurementioning
confidence: 99%
“…Active packaging and nanosensor systems. EC sensor systems are in development for incorporation into polymers, potentially leading to creation of an easy-to-use test material that produces a visible color change upon contact with a target compound (217,218). One potential application for this sensor system is in portable test kits for food inspectors where EC can be detected by mixing a sample (e.g., distilled spirits or wine) with a sensor-enabled test material for rapid analysis.…”
Section: Sers Sers Technology Has Been Utilized In Researchmentioning
confidence: 99%